Exploring the Co-occurrence of Manual Verbs and Actions in Early Mother-Child Communication - Rodrigo, María José; Muñetón-Ayala, Mercedes; de Vega, Manuel (Frontiers in Psychology, 2020)
The embodiment approach has shown that motor neural networks are involved in the processing of action verbs. There is developmental evidence that embodied effects on verb processing are already present in early years. Yet, the ontogenetic origin of this motor reuse in action verbs remains unknown. This longitudinal study investigates the co-occurrence of manual verbs and actions during mother-child daily routines (free play, bathing and dining) when children were 1 to 2 (Group 1) and 2 to 3 (Group 2) years old. Eight mother-child dyads were video-recorded in three-month intervals across 12 months (27 recording hours), and the timing of verbs and manual actions (21,876 entries) were coded by independent observers. Results showed that the probability of matched verb-action co-occurrences were much higher (0.80 and 0.77) than that of random co-occurrences (0.13 and 0.15) for Group 1 and Group 2, respectively. The distributions of the verb-action temporal intervals in both groups were quite symmetrical and skewed with the peak corresponding to both synchronic intervals (8% of the cases) and the shortest + 5 sec interval (40% of the cases). Mother-led instances occurred in both groups whereas child-led instances were restricted to Group 2. Mothers pragmatically aligned their verbal productions, since they repeatedly used (74%) those verbs they shared with their children’s repertoire (31%). In conclusion, the early multisensory communicative and manipulative scene affords grounding of verb meanings on the ongoing actions, facilitating verb-action pairing in the realm of social interactions, providing a new dimension to the prevailing solipsistic approach to embodiment.